Commentaries on the U.P. Urban Buildings (Regulation of Letting, Rent & Eviction) Act, 1972 (Act No. 13 of 1972) : as amended up-to-date, alongwith up-to-date rules, notifications & other allied laws - Srivastava, Surya Prasad, 1912- (Alia Law Agency, 1982)
Includes case laws and statutes laws till December, 1981.